A Philosophical Study of Agricultural Image Processing Techniques - J, Valarmathi; V T, Kruthika (Buana Information Technology and Computer Sciences (BIT and CS), 2023)
The development of agriculture in China has been substantially aided by the development of image processing technologies. It is simple for people to comprehend the significance of image processing technology for agricultural development by presenting the application status of image processing technology in agriculture and its impact on agricultural production value. This research examines how image processing technology is used in agriculture on the basis of that information. This study first examines how image processing technology is used in the world of agriculture. Second, this study applies both classic machine recognition technology and image processing technology to crop pest identification, analyses their effects, and highlights the application effect of image processing technology in the agricultural industry. The findings indicate that this approach has a recognition rate of 86%, 89%, 91%, 83%, 78%, and 79%, respectively. It is evident that the detection of crop diseases and insect pests is improved by the use of image processing technology.